СУЧАСНИЙ СТАН СТВОРЕННЯ, ВИРОБНИЦТВА ТА ДОСЛІДЖЕННЯ ТАБЛЕТОВАНИХ ЛІКАРСЬКИХ ПРЕПАРАТІВ Повідомлення 20. Характеристика процесу створення та дослідження гастроретентивних систем доставки лікарських речовин. - Demchuk, M. B.; Darzuli, N. P.; Hroshovyi, T. A.; Demchuk, S. V. (Фармацевтичний часопис, 2016)
MODERN STATE OF CREATION, PRODUCTION AND RESEARCH OF DRUGS M.B. Demchuk, N.P. Darzuli, T.A. Hroshovyi, S.V. Demchuk1 TernopilStateMedicalUniversityby I.Ya. Horbachevsky 1JSC “Ternopharm” Notice 20. The characteristic of process of creating and research of gastroretentive drug delivery system. Summary: the literature on the benefits of the use and technological aspects of obtaining gastroretentive drug delivery system, such as floating, high density (sinking), mucoadhesive and magnetic systems, super porous hydrogel and matrix systems are summarized. Keywords: gastroretentive drug delivery system, gastrointestinal tract, intragastric floating systems. Introduction. Oral administration is the most convenient and preferred means of any drug delivery to the systematic circulation. Dosage forms with a prolonged gastric residence time, i.e. gastro retentive dosage forms (GRDFs), will provide us with new and important therapeutic options. GRDFs extend significantly the period of time over which the drug may be released. Thus, they not only prolong dosing intervals, but also increase patient compliance beyond the level of existing controlled release dosage forms. Gastroretentive drug delivery is an approach to prolong gastric residence time, thereby targeting site-specific drug release in the upper gastrointestinal tract for local or systemic effects. Prolonged gastric retention improves bioavailability, reduces drug waste, and improves solubility for drugs that are less soluble in a high pH environment. It has applications also for local drug delivery to the stomach and proximal small intestine. The most important parameters which has impact on the gastric retention time of oral dosage forms include: density, size and shape of the dosage form, food intake and its nature, caloric content and frequency of intake, posture, gender, age, sex, sleep, body mass index, physical activity and diseased states of the individual (e.g. chronic disease, diabetes etc.) and administration of drugs with impact on gastrointestinal transit time. Various attempts have been made to retain the dosage form in the stomach as a way of increasing the retention time. These attempts include introducing floating dosage forms (gas-generating systems and swelling or expanding systems), mucoadhesive systems, high-density systems, modified shape systems, gastric- emptying delaying devices and co administration of gastric emptying delaying drugs. Floating drug delivery systems have a bulk density less than gastric fluids and so remain buoyant in the stomach without affecting gastric emptying rate for a prolonged period of time. While the system is floating on the gastric contents, the drug is released slowly at the desired rate from the system. Floating drug delivery systems can be divided into non effervescent and gasgenerating (effervescent) system. High density (sinking) or non- floating drug delivery systems have the density that must exceed density of normal stomach content ( 1.004 gm/cm3). These formulations are prepared by coating drug on a heavy core or mixed with inert materials such as iron powder, barium sulphate, zinc oxide and titanium oxide etc. Bioadhesive drug delivery systems (BDDS) are used as a delivery device within the lumen to enhance drug absorption in a site specific manner. This approach involves the use of bioadhesive polymers, which can adhere to the epithelial surface in the stomach. Materials commonly used for bioadhesion are polyacrylic acid, chitosan, cholestyramine, sodium alginate, hydroxypropyl methylcellulose, sucralfate, tragacanth, dextrin, polyethylene glycol and polylactic acids etc. Super porous hydrogel systems. In this approach to improve gastric retention time super porous hydrogels of average pore size >100 micro miter, swell to equilibrium size within a minute due to rapid water uptake by capillary wetting through numerous interconnected open pores. Magnetic systems. This approach to enhance the gastric retention time is based on the simple principle that the dosage form contains a small internal magnet, and a magnet placed on the abdomen over the position of the stomach. Conclusions. The basic requirements and approaches to the development of gastroretentive drug delivery systems and examples to obtain tablets that can be kept for a long time in the stomach are considered. References 1. Garg R. Progress in sontrolled gastroretentive delivery systems / R Garg, GD Gupta // Tropical Journal of Pharmaceutical Research. – 2008. - №7(3). – R.1055-1066. 2. Review on gastroretentive drug delivery system / A. Badoni I, A. Ojha, G. Gnanarajan et al. // The pharma innovation. – 2012. - Vol.1, № 8. – R.32-42. 3. AReview on gastroretentive drug delivery system / Pranav Joshi, Priyank Patel,Hiren Modi et al. // International Journal of Pharmaceutical Science and Bioscientific Research. – 2012. – Vol. 2, Issue 3. – P.123-128. 4. Streubel A. Drug delivery to the upper small intestine window using gastroretentive technologies / Streubel A, Siepmann J, Bodmeier R. // Curr Opin Pharmacol. – 2006. - №6. – R.501-508. 5. Floating drug delivery systems: A review / Arrora S, Ali J, Khar RK et al. // AAPS Pharm Sci Tech. – 2005. - №6(3). – R. 372-390. 6. Nasa P. Floating systems: a novel approach towards gastroretentive drug delivery systems / Praveen Nasa, Sheefali Mahant, Deepika Sharma // International Journal of Pharmacy and Pharmaceutical Sciences. – 2010. - Vol 2, №3. – R. 2-7. 7. Gastroretentive drug delivery systems: A review of formulation approaches / P. Rathee, M. Jain, S. Rathee et al. // The pharma innovation. – 2012. - Vol.1, № 8. – R.79 - 107. 8. Swetha S. A Comprehensive review on gastroretentive drug delivery systems / Sandina Swetha, Ravi Teja Allena, DV. Gowda // International Journal of Research in Pharmaceutical and Biomedical Sciences. – 2012. - Vol. 3 (3). – R. 1285-1293. 9. Amit Kumar Nayak Gastroretentive drug delivery systems: a review / Amit Kumar Nayak, Ruma Maji, Biswarup Das // Asian Journal of Pharmaceutical and Clinical Research. - 2010. - Vol.3, Iss. 1. – R.2-10. 10. Jaimini M. Formulation and evaluation of famotidine floating tablets / Jaimini M., Rana AC., Tanwar YS. // Current drug delivery. – 2007. - №4. –R.51-55. 11. Development, in-vitro evaluation & study of effect of hardness on buoyancy time of gastro retentive floating tablets of famotidine / Akbari B.V., Dholakiya R.B., Shiyani B.G. et al. // Journal of Pharmacy Research. – 2009. - №2(10). – R.1579-1583. 12. Abeda Aqther Formulation and in-vitro evaluation of ornidazole gastroretentive tablets by using low density swellable polymers / Abeda Aqther, B. Pragati kumar, Peer Basha // Indian Journal of Research in Pharmacy and Biotechnology. – 2013. - № 1(5). - P.597-601. 13. Formulation and evaluation of gastroretentive tablets of furosemide (Evaluation based on drug release kinetics and factorial designs) / Deepak Jain, Sofiya Verma, Shashi Bharti Shukla et al. // J. Chem. Pharm. Res. – 2010.- №2(4). – R.935-978. 14. Rakesh Pahwa Floating granules of metformin hydrochloride: preparation and optimization using factorial design / Rakesh Pahwa, Seema Bisht, Vipin Kumar // Bulletin of Pharmaceutical Research. - 2012. - №1. – R.42. 15. Rakesh Pahwa Formulation and characterization of glipizide loaded floating microspheres / Rakesh Pahwa, Nidhi Saini, Neeta, Vipin Kumar // Bulletin of Pharmaceutical Research. - 2012. - №1. – R.44. 16. Formulation and evaluation of sitagliptin phosphate gastroretentive tablets / Krishna Keerthi Brahmandam, Sasikanth Kothamasu, Anitha Makineni et al. // Carib.j.SciTech. – 2014.- Vol.2. – P. 270-281. 17. Preparation and evaluation of gastroretentive floating tablets of mebendazole / Krunal Patel, Biswajit Biswal., Nabin Karna et al. // International Journal of Current Pharmaceutical Research. – 2011. - Vol 3, Issue 1. – P.63-65. 18. Omray L. K. Design of gastroretentive drug delivery system of diltiazem hydrochloride / L. K. Omray // International Journal of Pharma Sciences and Research. – 2014. - Vol 5., №2. – R.16-19. 19. Ghugarkar P. Advances in gastroretentive drug delivery system: a review / Ghugarkar P. // World Journal of Pharmacy and Pharmaceutical Sciences. – 2015. – Vol. 4, Issue 07. – P.512-521. 20. Ashok Ch. M. Development and in vitro evaluation of gastroretentive high density tablet of propafenone hcl / Chordiya Mayur Ashok, Senthil Kumaran K, Gangurde Hemant Hiraman // Asian J Pharmaceut Res Health Care. – 2013. – Vol.2, №5. – P.89-99. 21. Saikh Mahammed Athar Alli Developing gastro retentive tablets: prospective planning / Saikh Mahammed Athar Alli // Inter. J. of Pharmacotherapy. – 2014. - №4(1). – R.36-42. 22. Gastroretentive drug delivery system of a lipid lowering agent / D. Krishnarajan, N. Senthil Kumar, R.Yadav // International Current Pharmaceutical Journal. – 2013. - №2(9). – R.152-155. 23. Ankit Anand Kharia Formulation and evaluation of gastroretentive drug delivery system of acyclovir as mucoadhesive nanoparticles / Ankit Anand Kharia, Akhlesh Kumar Singhai // International Journal of PharmTech Research. – 2013. - №5(4). – R. 1538-1545. 24. Jivani R. R. Design and development of a self correcting monolithic gastroretentive tablet of baclofen / R.R. Jivani, Ch.N. Patel, N.P. Jivani // Sci Pharm. – 2009. - №77. – R. 651–667. 25. Makarova O.H. Vybor polymerov dlya sozdanyya matrychnoy platformy hastroretentyvnykh tabletok / O.H. Makarova, V.F. Turetskova // Fundamental research. – 2013. - №1. – S.458-462. 26. Hromova L.Y. Hastroretentyvnye tabletky atsyklovyra na osnove synerhychesky vzaymodeystvuyushchykh polysakharydov / L.Y. Hromova, D. Khoykhman, Y. Sela // Khymyko-farm. zhurn. – 2007. – T.41, №12. – S. 34-36. 27. Rezhym dostupu: http://www.prnewswire.com/news-releases/endorex-presents-drug-delivery-and-cancer-product-updates-at-european-conference-74154997.html